Preparation method of carbon dot-based composite photocatalyst capable of degrading organic dye
By combining carbon dots R-CDs with CeO2 material to form R-CDs/CeO2 composite photocatalysts, the problem of insufficient absorption capacity of existing photocatalysts in visible light areas is solved, and the organic dyes in printing and dyeing wastewater is efficiently degraded, which has improved the Material stability and degradation efficiency.
Patent Information
- Application Number
- CN202411437179.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing photocatalysts have insufficient absorption capacity in the visible light area, which leads to their unsatisfactory degradation efficiency of organic dyes in printing and dyeing wastewater, and their stability and preparation costs are high, which limits their widespread use in practical applications.
By combining carbon dots R-CDs with CeO2 material, an R-CDs/CeO2 composite photocatalyst is formed, and prepared by hydrothermal and solvothermal reaction methods, the conductive properties and photocatalytic activity of the material are optimized, its spectral response range is expanded, and photocatalytic is improved. efficiency.
The photoresponse and adsorption properties of the photocatalyst are significantly improved, and the organic dyes in the printing and dyeing wastewater can be efficiently degraded, with a degradation efficiency of more than 98%, and the material stability and preparation cost are improved.
Smart Images

Figure CN119114049A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts, and in particular to a method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes. Background Art
[0002] The textile printing and dyeing industry is a key industry in China, producing hundreds of millions of textiles annually. However, the printing and dyeing wastewater produced contains a large amount of harmful substances, such as organic dyes and heavy metal ions, which pose a serious threat to the environment and human health. To address this problem, researchers are working to develop effective wastewater treatment technologies. The main treatment methods currently include adsorption, coagulation, biological treatment and photocatalytic degradation. Photocatalytic degradation has attracted widespread attention because it uses solar energy, directly converts pollutants into harmless substances, and is not prone to secondary pollution. It has become a popular research direction for solving printing and dyeing wastewater pollution.
[0003] There are many types of photocatalysts, including inorganic materials, organic materials, and composite materials. In recent years, semiconductor-based multiphase photocatalytic oxidation technology has shown significant efficiency in removing inorganic and organic pollutants and has become a research hotspot, especially cerium oxide (CeO 2 ), has attracted much attention due to its high oxygen storage capacity, high energy conduction band, high oxidation ability, high catalytic activity and chemical stability. 2 The light absorption of CeO is mainly concentrated in the ultraviolet region, the visible light absorption is insufficient, and the recombination rate of photogenerated electron-hole pairs is fast, which limits its photocatalytic efficiency. 2 In order to improve the photocatalytic performance of carbon dots, researchers have adopted a variety of strategies, such as precious metal deposition, dye sensitization, metal and non-metallic element doping, etc. Among them, as an emerging carbon-based nanomaterial, carbon dots (CDs) have excellent conductivity and chemical stability, can effectively capture light energy in a wider band, and serve as a transmission channel for electrons and holes, effectively inhibiting the recombination of photogenerated carriers. In recent years, the construction of carbon dot composite semiconductor materials has become one of the research hotspots for chemists and environmental workers, and it is of great significance to the study of efficient degradation of printing and dyeing wastewater.
[0004] In the field of photocatalysis, CDs / CeO 2 The composite material exhibits remarkable performance due to its unique physical and chemical properties. 2 As a material with excellent oxygen storage capacity and redox properties, CeO usually has strong absorption capacity in the ultraviolet region, but insufficient absorption in the visible region, which limits its efficiency in the photocatalytic process. 2The rapid recombination of photogenerated electron-hole pairs in the photocatalytic system also leads to its unsatisfactory photocatalytic efficiency. However, when combined with carbon dots to form a composite material, its absorption band of light can be significantly expanded, thereby improving the photocatalytic efficiency. By precisely controlling the size and surface functional groups of carbon dots, the conductive properties and photocatalytic activity of the composite material can be optimized, thus playing an important role in electronic devices, sensors and other fields. 2 Composite materials have shown great potential in the field of photoelectrocatalysis, but they still face challenges in practical applications, such as improving stability and durability, reducing preparation costs, and large-scale production. Future research needs to focus on how to solve these problems through innovative synthesis strategies and material design to maximize the performance of composite materials and expand their application.
[0005] Therefore, in view of the above situation, the present invention develops a R-CDs / CeO 2 Composite photocatalysts can enrich the current deficiencies in the application of composite photocatalysts in the treatment of organic dyes in printing and dyeing wastewater. Combining emerging photocatalytic technology, R-CDs with conversion function and CeO 2 The material composite is used for photoelectrocatalytic degradation under ultraviolet and visible light, providing a new strategy for printing and dyeing wastewater treatment. Summary of the invention
[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes, thereby efficiently degrading organic dyes in printing and dyeing wastewater.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a carbon dot-based composite photocatalyst capable of degrading organic dyes comprises the following steps:
[0009] (1) Preparation of carbon dots R-CDs:
[0010] The p-aminophenol hydrochloride is fully dissolved in water and stirred vigorously, and then the mixture is transferred to a polytetrafluoroethylene-lined steel autoclave for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled, and then the reactant is filtered through a mixed cellulose ester filter membrane, and the obtained filtrate is concentrated. Then, a mixed liquid consisting of methanol, isopropanol and n-hexane is used as a mobile phase, and the concentrated liquid is separated and purified by a chromatographic column to obtain the desired R-CDs;
[0011] (2) R-CDs / CeO 2 Preparation of composite photocatalyst:
[0012] CeO 2The nanopowder is dissolved in a mixed solution of R-CDs and anhydrous ethanol, stirred thoroughly to completely dissolve, and then the mixture is transferred to a steel autoclave lined with polytetrafluoroethylene for solvothermal reaction. After the reaction is completed, it is naturally cooled, and then the mixed solution in the autoclave is transferred into a centrifuge tube for centrifugation to obtain a sediment. The sediment is then washed once with distilled water and anhydrous ethanol, and dried in a vacuum oven. The dried sediment is then pyrolyzed in a nitrogen atmosphere to obtain the desired R-CDs / CeO 2 Composite photocatalyst.
[0013] Furthermore, in step (1), the ratio of the amount of p-aminophenol hydrochloride to water is (0.8-1.0) g: (146-154) mL;
[0014] The vigorous stirring time is 4-6 minutes.
[0015] Furthermore, in step (1), the temperature of the hydrothermal reaction is 170-190° C., and the time is 3-5 hours.
[0016] Furthermore, in step (1), the filtrate is concentrated to 38-42 mL.
[0017] Furthermore, in step (1), the volume ratio of methanol, isopropanol and n-hexane in the mobile phase is 1:(6-8):1.
[0018] Furthermore, in step (2), the CeO 2 The usage ratio of nano powder, R-CDs, and anhydrous ethanol is (0.9-1.1) g: (18-22) mL: (7-13) mL;
[0019] The sufficient stirring time is 8-12 minutes.
[0020] Furthermore, in step (2), the temperature of the solvent thermal reaction is 190-210° C. and the time is 2-4 hours.
[0021] Furthermore, in step (2), the centrifugal speed is 7000-9000 rpm and the time is 5-10 min.
[0022] Furthermore, in step (2), the drying temperature is 50-70° C. and the drying time is 18-30 hours.
[0023] Furthermore, in step (2), the pyrolysis temperature is 470-530° C. and the time is 3-5 h.
[0024] The beneficial effects of the present invention are:
[0025] The present invention combines R-CDs with CeO2 to form R-CDs / CeO 2 Composite materials can significantly improve CeO 2 The photoresponse performance of R-CDs / CeO 2 The composite material has an enhancing effect in the photocatalytic degradation of pollutants, significantly inhibiting the recombination of photogenerated carriers, broadening the spectral response range, and enhancing the adsorption performance of the photocatalyst, thereby significantly improving the photocatalytic efficiency and can efficiently degrade organic dyes in printing and dyeing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The R-CDs / CeO prepared by the present invention 2 SEM image of the composite photocatalyst, showing a uniform spherical morphology with mixed particle sizes;
[0027] Figure 2 The R-CDs / CeO prepared by the present invention 2 HRTEM image of the composite photocatalyst, in which it can be observed that some of the 2 R-CDs on. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] A method for preparing a carbon dot-based composite photocatalyst capable of degrading organic dyes comprises the following steps:
[0031] (1) Preparation of carbon dots R-CDs:
[0032] 0.8 g of p-aminophenol hydrochloride was fully dissolved in 146 mL of water and stirred vigorously for 4 min. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave for hydrothermal reaction at 170 ° C for 5 h. After the reaction was completed, it was naturally cooled and then filtered through a mixed cellulose ester filter membrane with a pore size of 0.22 μm. The obtained filtrate was concentrated to 38 mL. A mixed solution of methanol, isopropanol and n-hexane in a volume ratio of 1:6:1 was used as the mobile phase. The concentrate was separated and purified by a chromatographic column to obtain the desired carbon dots R-CDs.
[0033] (2) R-CDs / CeO 2 Preparation of composite photocatalyst:
[0034] 0.9gCeO 2 The nanopowder was dissolved in a mixed solution consisting of 18 mL of the carbon dots R-CDs prepared in step (1) above and 7 mL of anhydrous ethanol, and stirred for 8 min to completely dissolve it. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave and subjected to a solvent thermal reaction at 190 ° C for 4 h. After the reaction was completed, the mixture was naturally cooled. The mixed solution in the autoclave was then transferred to a centrifuge tube and centrifuged at 7000 rpm for 10 min to obtain a precipitate. The precipitate was then washed once with distilled water and anhydrous ethanol, and dried in a vacuum oven at 50 ° C for 30 h. The dried precipitate was then pyrolyzed in a nitrogen atmosphere at 470 ° C for 5 h to obtain the desired R-CDs / CeO 2 Composite photocatalyst.
[0035] Embodiment 2:
[0036] A method for preparing a carbon dot-based composite photocatalyst capable of degrading organic dyes comprises the following steps:
[0037] (1) Preparation of carbon dots R-CDs:
[0038] 0.9 g of p-aminophenol hydrochloride was fully dissolved in 150 mL of water and stirred vigorously for 5 min. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave for hydrothermal reaction at 180 ° C for 4 h. After the reaction was completed, the mixture was naturally cooled and filtered through a mixed cellulose ester filter membrane with a pore size of 0.22 μm. The filtrate was concentrated to 40 mL. A mixed solution of methanol, isopropanol and n-hexane in a volume ratio of 1:7:1 was used as the mobile phase. The concentrate was separated and purified by a chromatographic column to obtain the desired carbon dot R-CDs.
[0039] (2) R-CDs / CeO 2 Preparation of composite photocatalyst:
[0040] 1.0gCeO 2 The nanopowder was dissolved in a mixed solution consisting of 20 mL of the carbon dots R-CDs prepared in step (1) above and 10 mL of anhydrous ethanol, and stirred for 10 min to completely dissolve it. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave and subjected to a solvent thermal reaction at 200 ° C for 3 h. After the reaction was completed, the mixture was naturally cooled. The mixed solution in the autoclave was then transferred to a centrifuge tube and centrifuged at 8000 rpm for 8 min to obtain a sediment. The sediment was then washed once with distilled water and anhydrous ethanol, and dried in a vacuum oven at 60 ° C for 24 h. The dried sediment was then pyrolyzed in a nitrogen atmosphere at 500 ° C for 4 h to obtain the desired R-CDs / CeO 2 Composite photocatalyst.
[0041] Embodiment 3:
[0042] A method for preparing a carbon dot-based composite photocatalyst capable of degrading organic dyes comprises the following steps:
[0043] (1) Preparation of carbon dots R-CDs:
[0044] 1.0 g of p-aminophenol hydrochloride was fully dissolved in 154 mL of water and stirred vigorously for 6 min. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave for hydrothermal reaction at 190 ° C for 3 h. After the reaction was completed, it was naturally cooled and then filtered through a mixed cellulose ester filter membrane with a pore size of 0.22 μm. The obtained filtrate was concentrated to 42 mL. A mixed solution of methanol, isopropanol and n-hexane in a volume ratio of 1:8:1 was used as the mobile phase. The concentrate was separated and purified by a chromatographic column to obtain the desired carbon dot R-CDs.
[0045] (2) R-CDs / CeO 2 Preparation of composite photocatalyst:
[0046] 1.1gCeO 2 The nanopowder was dissolved in a mixed solution of 22 mL of the carbon dots R-CDs prepared in step (1) above and 13 mL of anhydrous ethanol, and stirred for 12 min to completely dissolve it. The mixture was then transferred to a polytetrafluoroethylene-lined steel autoclave and subjected to a solvent thermal reaction at 210 ° C for 2 h. After the reaction was completed, the mixture was naturally cooled. The mixed solution in the autoclave was then transferred to a centrifuge tube and centrifuged at 9000 rpm for 5 min to obtain a sediment. The sediment was then washed once with distilled water and anhydrous ethanol, and dried in a vacuum oven at 70 ° C for 18 h. The dried sediment was then pyrolyzed in a nitrogen atmosphere at 530 ° C for 3 h to obtain the desired R-CDs / CeO 2 Composite photocatalyst.
[0047] Test example:
[0048] Taking methylene blue (MB) as the degradation target, the R-CDs / CeO prepared in Examples 1-3 were subjected to 2 Composite photocatalysts, R-CDs, CeO 2The photocatalytic performance of a single photocatalyst was tested. The light source used was a 300W xenon lamp to ensure the progress of the photocatalytic reaction. There was a water layer between the lamp and the reaction system to avoid the thermal effect of light. The experimental process was carried out at room temperature. The specific steps are summarized as follows: 0.08g of photocatalyst powder / 3mL of R-CDs solution was evenly dispersed in 80mL of 10mg / L MB dye solution to form a uniform suspension. The suspension was continuously stirred for 30min under lightless conditions to ensure that the adsorption-desorption equilibrium between the photocatalyst and the MB dye was reached. The suspension was irradiated with a xenon lamp. 3mL of the mixed solution was taken each time within the specified time, filtered, and then poured into a cuvette for analysis using a UV-visible spectrophotometer. The absorbance (A) at 665nm was recorded. The corresponding concentration (C) was obtained based on the absorbance data (A). t ).
[0049] From the degradation experiments, the dye removal efficiency (η, %) was then calculated using the following formula:
[0050] η=(C 0 -C t ) / C 0 ×100%
[0051] In the formula, C 0 and C t are the initial and tested concentrations of MB (mg / L).
[0052] R-CDs / CeO prepared in Example 1-3 2 Composite photocatalysts and individual R-CDs and CeO 2 The removal efficiency of methylene blue by photocatalyst is shown in the following table:
[0053] Different catalysts Methylene blue removal efficiency η(%) <![CDATA[The R-CDs / CeO prepared in Example 1 2 Composite photocatalyst]]> 98.52 <![CDATA[The R-CDs / CeO prepared in Example 2 2 Composite photocatalyst]]> 98.76 <![CDATA[The R-CDs / CeO prepared in Example 3 2 Composite photocatalyst]]> 98.65 R-CDs 74.24 <![CDATA[CeO 2 ]]> 67.97
[0054] The above results show that the R-CDs / CeO 2 The composite photocatalyst has a better removal efficiency for methylene blue, which can reach more than 98%. 2 The composite photocatalyst has excellent photocatalytic performance and photocatalytic efficiency, and can effectively degrade methylene blue in printing and dyeing wastewater.
[0055] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes, characterized in that: The following steps are involved: (1) Preparation of carbon dots R-CDs: The p-aminophenol hydrochloride is fully dissolved in water and stirred vigorously, and then the mixture is transferred to a polytetrafluoroethylene-lined steel autoclave for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled, and then the reactant is filtered through a mixed cellulose ester filter membrane, and the obtained filtrate is concentrated. Then, a mixed liquid consisting of methanol, isopropanol and n-hexane is used as a mobile phase, and the concentrated liquid is separated and purified by a chromatographic column to obtain the desired carbon dot R-CDs; (2) Preparation of R-CDs / CeO2 composite photocatalyst: The CeO2 nanopowder is dissolved in the mixed solution of the carbon dots R-CDs and anhydrous ethanol obtained in step (1), and stirred thoroughly to make it completely dissolved. Then, the mixture is transferred to a polytetrafluoroethylene-lined steel autoclave for solvothermal reaction. After the reaction is completed, it is naturally cooled. Then, the mixed solution in the autoclave is transferred to a centrifuge tube for centrifugation to obtain a sediment. The sediment is then washed once with distilled water and anhydrous ethanol, and dried in a vacuum oven. Then, the dried sediment is pyrolyzed in a nitrogen atmosphere to obtain the desired R-CDs / CeO2 composite photocatalyst.
2. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (1), the ratio of p-aminophenol hydrochloride to water is (0.8-1.0) g: (146-154) mL; The vigorous stirring time is 4-6 minutes.
3. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 170-190° C. and the time is 3-5 hours.
4. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (1), the filtrate is concentrated to 38-42 mL.
5. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (1), the volume ratio of methanol, isopropanol and n-hexane in the mobile phase is 1:(6-8):
1.
6. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (2), the usage ratio of CeO2 nanopowder, R-CDs and anhydrous ethanol is (0.9-1.1) g: (18-22) mL: (7-13) mL; The sufficient stirring time is 8-12 minutes.
7. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (2), the temperature of the solvent thermal reaction is 190-210° C. and the time is 2-4 hours.
8. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (2), the centrifugal speed is 7000-9000 rpm and the time is 5-10 min.
9. The method for preparing a carbon-dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (2), the drying temperature is 50-70°C and the drying time is 18-30 hours.
10. The method for preparing a carbon dot-based composite photocatalyst capable of degrading organic dyes according to claim 1, characterized in that: In step (2), the pyrolysis temperature is 470-530° C. and the time is 3-5 hours.
